Cover, Content, and Editorial Note from Anterior J Vol. 18 No. 2 June 2019 - Chief Editor of Anterior J (Anterior Jurnal, 2019)
Assalamu’alaikum Wr. Wb.Dear reader, now ANTERIOR JURNAL re-published on Volume 18 Issue 2 June 2019. The success of this publication is the result of good cooperation of all parties who maintain the publishing sustainability twice a year. This edition is also our latest edition, publishing articles with a multidisciplinary scope, starting from volume 19 Issue 1 December 2019, all articles in the ANTERIOR JURNAL are only focused on the Social-Humanities scope, covering all fields of education, social and political, Islamic studies and other relevant topics. In this edition, we are still publishing four articles in the field of agrotechnology and engineering, which will be the last time we publish articles in the field of science at the ANTERIOR JURNAL.Alhamdulillah, from this edition ANTERIOR JURNAL achieved a new milestone by publishing two English-language articles. We hope this will be a step forward for the future internationalization of the Journal.The publication of ANTERIOR JURNAL certainly participates in disseminating the results of research and review of science and technology development conducted by lecturers and researchers especially from UM Palangkaraya and other universities.This edition contains 12 articles consisting of Education, Social and Political, Islamic Studies, Engineering, and Agrotechnology topics. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions.The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the success of the publication in the next edition in December 2019. Wassalamu’alaikum Wr. Wb.